What Makes Spiders Frightening and Disgusting to People? - Zvaríková, Martina; Prokop, Pavol; Zvarík, Milan; Ježová, Zuzana; Medina-Jerez, William; Fedor, Peter (Frontiers in Ecology and Evolution, 2021)
The quality of human-animal interactions may crucially influence conservation efforts. Unfortunately, some animals are considered notoriously unpopular by the people, despite their play important roles in ecosystem functioning and ecosystem services. Using forced-choice paradigm, we investigated which cues consider humans frightening and disgusting in spiders, one of most unpleasant animals in the world. The research was carried out with a representative sample of N = 1015 Slovak adults. We found that perceived fear and disgust of spiders was triggered predominantly by enlarged chelicerae, abdomen and the presence of body hair. Longer legs were associated with perceived fear, but the presence of two eyes did not provide any statistical significance. We hope that further research in this field where will be manipulated additional cues (e.g. colour, number of legs), can improve conservation efforts by means of improved reputation of spiders in the eyes of general public.